Meningkatkan Kesadaran Masyarakat Untuk Menjadi Pelaku Usaha Yang Inovatif dan Kreatif Melalui FGD - Wibowo, Ridho Andira; Pratama, Teddy Yogi; Aprilia, Nadia; S, Azzahra Tri Najla; Hasibuan, Nasyuwah Sabila; Sari, Rina Filia (Universitas Islam Negeri Sumatera Utara, 2024)
This scientific article aims to examine how the participation of the Sidourip Village community in the development of waste-based handicraft and agriculture businesses can increase awareness and role as innovative and creative entrepreneurs. This research was conducted in Sidourip Village, Beringin District, Deli Serdang Regency during the service period from July 18 to August 18, 2023. This research uses a Participatory Action Research (PAR) approach that involves a series of Focus Group Discussions (FGD) as a method to explore in-depth understanding of community participation dynamics, the role of the 2023 UINSU KKN Program, and the potential for economic transformation through waste-based business development. The sample of this study involves several heads of families from 4 hamlets with different economic backgrounds. The results of this study show that FGD can be an effective platform for stimulating community creativity and innovation in processing waste into valuable products. This research also illustrates that the 2023 UINSU KKN Program has an important role as an agent of change supporting local economic transformation. Thus, this research provides a significant contribution to sustainable local economic development through the utilization of cloth and agricultural waste in Sidourip Village.